The prevalence and trends of waterpipe tobacco smoking: A systematic review. - Mohammed Jawad; Rana Charide; Reem Waziry; Andrea Darzi; Rami A Ballout; Elie A Akl (PLoS ONE)
Introduction Waterpipe tobacco smoking is harmful to health however its prevalence estimates remain uncertain. We aimed to systematically review the medical literature on waterpipe tobacco prevalence and trends. Methods We searched Medline, Embase and ISI Web of Science for 'waterpipe' and its synonyms, without using language or date restrictions. We included any measure of waterpipe tobacco smoking prevalence in jurisdictionally representative populations. We stratified findings by prevalence measure (past 30 day, ever, regular or occasional, daily, other or unspecified) and age (adults or youth). Results We included 129 studies reporting 355 estimates for 68 countries. In general, prevalence estimates among adults were highest in the Eastern Mediterranean, and among youth were about equal between Eastern Mediterranean and European regions. Past 30 day use was highest among Lebanese youth (37.2% in 2008), ever use was highest among Lebanese youth in 2002 and Lebanese university students in 2005 (both 65.3%), regular or occasional use was highest in among Iranian university students (16.3% in 2005), and daily use was highest among Egyptian youth (10.4% in 2005). Trend data were limited but most studies reported increased use over time, ranging from 0.3-1.0% per year among youth in the US to 2.9% per year among youth in Jordan (both for past 30 day use). Results were similar for ever use trends. Turkey (2.3% in 2008 to 0.8% in 2010) and Iraq (6.3% in 2008 and 4.8% in 2012) both witnessed decreased waterpipe use. Conclusion Waterpipe tobacco smoking is most prevalent in Eastern Mediterranean and European countries, and appears higher among youth than adults. Continued surveillance will be important to assess and inform policy measures to control waterpipe tobacco use.